Complete laparoscopic total mesorectal excision with an intersphincteric resection and coloplasty pouch anal anastomosis for lower rectal cancer - Toiyama, Yuji (J Anus Rectum Colon, 2018)
This pilot study aimed to develop a new technique, complete laparoscopic total mesorectal excision (TME) with an intersphincteric resection (ISR) and coloplasty pouch anal anastomosis to avoid any further abdominal incision other than laparoscopic port sites, and to assess the impact on short-quality of life and oncological outcomes of this technique. After laparoscopic TME, large bowel was dissected at the level of the promontory. Then, laparoscopic construction of the coloplasty pouch was performed. Simultaneously, a rectal specimen with ISR was excised using the transanal approach. Coloplasty pouch was gently pulled from pelvic thorough anal and a hand-sewn coloplasty pouch anal anastomosis was created. We had performed 8 surgeries using the new technique. Though one patient developed pelvic infections, but intestinal continuity could be maintained and no local and distant recurrence was recognized in other patients. We foresee this novel approach to have significant clinical potential for lower rectal cancer patients with ISR.